2022
DOI: 10.53637/wgyr1275
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Impact of Animal Abuse: The Need for Legal Recognition of Abused Pets as Sentient Victims of Domestic Violence in Australia

Abstract: Awareness of the incidence and impact of domestic violence has increased in recent decades, along with community and legal recognition of the interests of animals. However, streams of jurisprudence addressing these issues have only partially influenced one another. While in most Australian jurisdictions, animal cruelty can constitute domestic violence, abused companion animals have not been accorded the legal status of victims. This article proposes introducing laws that recognise such animals as sentient vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…From Figure 4 , emotional and psychological characteristics directly affect risk appetite, affecting credit demand [ 23 ]. Using credit is a risky act.…”
Section: Methodsmentioning
confidence: 99%
“…From Figure 4 , emotional and psychological characteristics directly affect risk appetite, affecting credit demand [ 23 ]. Using credit is a risky act.…”
Section: Methodsmentioning
confidence: 99%
“…Many survivors of domestic violence (48%) are hesitant to escape their domestic violence environment due to the fact of being concerned about what will happen to their companion animal [ 126 ]. Further, it has been reported that approximately 18–48% of survivors have delayed entering a domestic violence shelter due to the presence of welfare concerns for their companion animals that they had to leave behind [ 47 , 109 , 113 , 121 , 127 ]. As a result, both companion animal and guardian safety and welfare is at risk, as most survivors remain within the domestic violence environment, not wishing to leave their companion animal behind and having limited safe refuge options that accept guardians with companion animals [ 106 , 107 , 128 ].…”
Section: Applying the Social Determinants Of Health To Companion Anim...mentioning
confidence: 99%
“…Care and welfare are a major concern when we talk about animals, and much like human healthcare, words can play an important role in outcomes (Valdez, 2021). The perception of animals as being sentient instead of property is directly and positively correlated with their improved treatment (Bagaric et al, 2022; Browning and Veit, 2022; Carlisle-Frank and Frank, 2006; Carlisle-Frank et al, 2004; Veevers, 1985). How individuals conceptualise their relationship with their companion animal (e.g.…”
Section: Ethical and Welfare Implications Of Termsmentioning
confidence: 99%